Vanadium salt inhibits osteoclast formation and preserves bone integrity in a rat model of type-1 diabetes associated bone loss - Joshua Greendyk; James Thornton; Darian Napoleon; Michael Greenberg; Anthony Lin; Mike Levidy; Jonathan R. Lopez; Maximilian Muñoz; Kevin Innella; Yazan Kadkoy; Maya Deza Culbertson; Jessica A. Cottrell; et al. (BioMetals, 2026)

Nature immersion in virtual reality has limited hypoalgesia effects for muscle pain or motor performance benefits during prescribed and self-regulated tasks - Callum A. O’Malley; David J. Harris; Sam W. Hughes; Jack E. Cottrell; Daniel Lloyd; Samuel J. Vine; Tom Arthur (European Journal of Applied Physiology, 2026)
Purpose Virtual reality (VR) reduces experimental and clinical pain, but whether these effects extend to naturally occurring muscle pain (NOMP) during exercise remains unclear. This study examined whether immersive nature-based VR attenuates NOMP and improves motor performance during prescribed and self-regulated exercise. Methods Two within-participant crossover studies were conducted involving 12 (Study 1) and 24 (Study 2) healthy participants. In Study 1, participants completed a stepped incremental cycling task to exhaustion. In Study 2, participants performed self-regulated intermittent isometric handgrip contractions at light (13/100) and strong (50/100) perceived effort. Tasks were completed under immersive VR (nature scene), two-dimensional sham, and no-intervention control conditions in pseudo-randomised, counterbalanced orders. Pain onset, NOMP intensity, perceived effort, and time to exhaustion were assessed in Study (1) Muscle pain intensity and force production were measured in Study (2) Repeated measures ANOVAs and assessed main condition effects. Results Immersive VR did not delay pain onset $$\:(p=.159)$$ , prolong time to exhaustion $$\:(p=.204)$$ , or lower perceived effort compared within sham or control conditions $$\:({p}^{{\prime\:}}s>.215)$$ . A small, yet practically meaningful, reduction in NOMP intensity occurred early during cycling $$\:({F}_{\text{2,22}}=4.518,p=.023,\:{\eta\:}_{p}^{2}=0.291[\text{0.002,0.500}\left]\right)$$ but was not sustained at later phases of the task $$\:({p}^{{\prime\:}}s . In Study 2, NOMP intensity $$\:(p=.815)$$ and force production measures $$\:({p}^{{\prime\:}}s were similar across conditions. Conclusion Nature-based immersive VR had limited effects on NOMP and motor performance. Pain types that are peripherally driven, like NOMP, may be less affected by VR interventions which target central mechanisms of pain modulation. Thus, hypoalgesia effects with VR are potentially pain-type dependent.

Seafood Sustainability Challenges for Import-Dependent Nations - Rosa Mar Dominguez-Martinez; Carissa J. Klein; Julia L. Blanchard; Anna Farmery; Caitlin D. Kuempel; Leslie Roberson; Scott Spillias; Richard S. Cottrell (Reviews in Fisheries Science & Aquaculture, 2026)

The effect of pressure on sulfur valence state in mafic silicate melts - Michelle J. Muth; Elizabeth Cottrell (Earth and Planetary Science Letters, 2025)

The Volcanoes of the World database - Benjamin J. Andrews; Edward Venzke; Elizabeth Cottrell; Sally S. K. Sennert; Kadie L. Bennis; A. E. J. Crafford (Bulletin of Volcanology, 2025)

3D reconstructions of stranded marine mammals via easily accessible remote sensing tools for use in morphometrics and visualizations - Brendan Cottrell; Margaret Kalacska; J. Pablo Arroyo-Mora; Oliver Lucanus; Paul Cottrell; Taylor Lehnhart; Stephen Raverty (Frontiers in Marine Science, 2025)
This study investigates the practicality and potential impact of three-dimensional (3D) scanning technology to assess marine mammal strandings. Mobile phones were used to evaluate the technology and its capability to accurately reconstruct topographic features of 11 distinct marine mammal species, across diverse environmental conditions. This process was validated by initially measuring an inflatable whale to an accuracy of greater than 99%, with most morphometrics collected being within 3% of conventional tape rule measurements. Our findings demonstrate the adaptability of the technology in remote environments, particularly for large whale strandings, while showcasing its utility to record morphometrics and enhance necropsy documentation. The study underscores the transformative role of 3D scanning in marine mammal postmortem examinations and conservation efforts, offering avenues for improved research, education, and management practices. It emphasizes the importance of accessible technology in engaging communities and advancing wildlife conservation efforts globally.

Harassment and killing of porpoises (“phocoenacide”) by fish‐eating Southern Resident killer whales ( Orcinus orca ) - Deborah A. Giles; Sarah J. Teman; Samuel Ellis; John K. B. Ford; Monika W. Shields; M. Bradley Hanson; Candice K. Emmons; Paul E. Cottrell; Robin W. Baird; Richard W. Osborne; Michael Weiss; David K. Ellifrit; et al. (Marine Mammal Science, 2024)
Endangered Southern Resident killer whales ( Orcinus orca ) are fish‐eaters that preferentially prey on adult Chinook salmon ( Oncorhynchus tshawytscha ). Despite being salmon specialists, individuals from all three killer whale pods (J, K, L) have been observed harassing and killing porpoises (family Phocoenidae) without consuming them. Retrospectively, we identified and analyzed 78 episodes of Southern Resident killer whales harassing porpoises between 1962 and 2020, of which 28 resulted in the porpoise's death (“phocoenacide”). Fifty‐six episodes involved harbor porpoise ( Phocoena phocoena ), 13 involved Dall's porpoise ( Phocoenoides dalli ), and the porpoise species was unreported for nine episodes. Southern Resident killer whales often targeted young porpoises that were similar in size to adult Chinook salmon. Both sexes participated in porpoise harassment. Juveniles engaged in the behavior the most; however, their rates of engagement were not found to differ significantly from most other age classes. The behavior was passed through generations and social groupings, as it was first observed in L pod and spread to the other two pods. Killer whales are highly complex animals known to exhibit social learning and cultural transmission of learned behaviors, but the reason(s) for this behavior is unknown. Hypotheses include the social and developmental benefits of play, hunting practice, or displaced epimeletic behavior.

Supplementing dietary betaine during late gestation increases plasma betaine and methionine concentrations in pregnant Merino ewes but not neonatal lambs - Billie-Jaye Brougham; Alice C. Weaver; Alyce M. Swinbourne; Jeremy J. Cottrell; Jennifer M. Kelly; David O. Kleemann; William H.E.J. van Wettere (Small Ruminant Research, 2024)

Aquaculture governance: five engagement arenas for sustainability transformation - Stefan Partelow; Furqan Asif; Christophe Béné; Simon Bush; Aisa O Manlosa; Ben Nagel; Achim Schlüter; Vishnumurthy M Chadag; Afrina Choudhury; Steven M Cole; Richard S Cottrell; Stefan Gelcich; et al. (Current Opinion in Environmental Sustainability, 2023)

Additive and non-additive genetic variance in juvenile Sitka spruce (Picea sitchensis Bong. Carr) - J.J. Ilska; D.J. Tolhurst; H. Tumas; J. P. Maclean; J. Cottrell; S.J. Lee; J. Mackay; J.A. Woolliams (Tree Genetics & Genomes, 2023)
Many quantitative genetic models assume that all genetic variation is additive because of a lack of data with sufficient structure and quality to determine the relative contribution of additive and non-additive variation. Here the fractions of additive ( f a ) and non-additive ( f d ) genetic variation were estimated in Sitka spruce for height, bud burst and pilodyn penetration depth. Approximately 1500 offspring were produced in each of three sib families and clonally replicated across three geographically diverse sites. Genotypes from 1525 offspring from all three families were obtained by RADseq, followed by imputation using 1630 loci segregating in all families and mapped using the newly developed linkage map of Sitka spruce. The analyses employed a new approach for estimating f a and f d , which combined all available genotypic and phenotypic data with spatial modelling for each trait and site. The consensus estimate for f a increased with age for height from 0.58 at 2 years to 0.75 at 11 years, with only small overlap in 95% support intervals ( I 95 ). The estimated f a for bud burst was 0.83 ( I 95 =[0.78, 0.90]) and 0.84 ( I 95 =[0.77, 0.92]) for pilodyn depth. Overall, there was no evidence of family heterogeneity for height or bud burst, or site heterogeneity for pilodyn depth, and no evidence of inbreeding depression associated with genomic homozygosity, expected if dominance variance was the major component of non-additive variance. The results offer no support for the development of sublines for crossing within the species. The models give new opportunities to assess more accurately the scale of non-additive variation.

No detectable redox exchange between sulfur and iron during rapid cooling of basalts - Michelle J. Muth; Elizabeth Cottrell (Earth and Planetary Science Letters, 2023)

Rebuilding A Collapsed Bivalve Population, Restoring Seagrass Meadows, and Eradicating Harmful Algal Blooms In A Temperate Lagoon Using Spawner Sanctuaries - Christopher J. Gobler; Michael H. Doall; Bradley J. Peterson; Craig S. Young; Flynn DeLaney; Ryan B. Wallace; Stephen J. Tomasetti; Timothy P. Curtin; Brooke K. Morrell; Elizabeth M. Lamoureux; Berry Ueoka; Andrew W. Griffith; et al. (Frontiers in Marine Science, 2022)
During the past century, bivalve populations across the globe have collapsed, resulting in negative ecosystem consequences due to their outsized impact on shallow estuaries. In response, there has been strong interest in the restoration of marine bivalve populations. Here, we present a decade-long restoration effort that sought to rebuild a collapsed (99.5% reduction in harvest) and recruitment-limited population of hard clams ( Mercenaria mercenaria ) in Shinnecock Bay, NY, USA, using spawner sanctuaries: no-harvest zones where adults were planted at high densities (~27 m- 2 ). Between 2012 to 2019, more than 3.2 million clams were planted in 64 discrete sanctuary plots (~1,850 m 2 each) located in zones with maximal larval retention and sediment and seawater characteristics that would maximize the conditioning and spawning of adults. Hydrodynamic models, quantification of hard clam larvae, and spatial recruitment patterns demonstrated larvae spawned within sanctuaries were transported to regions where clam densities significantly increased 18-fold over seven years (2015-2021; p <0.001) and harvests significantly increased more than 16-fold over nine years (2012-2021; p <0.0001). Increases in populations and harvests were caused by smaller clams recruited within the time frame of the creation of spawner sanctuaries. Higher clam densities caused biological filtration times of the bay to decrease from up to three months at the start of the project to as low as 10 days in 2021. Concurrently, concentrations of the harmful brown tide alga, Aureococcus anophagefferens , and chlorophyll a significantly decreased ( p <0.005) while water clarity and the extent of seagrass beds significantly increased ( p <0.05). Increases in clam landings and improvements in water quality were not observed in adjacent lagoonal estuaries where restoration did not occur. Given these outcomes and the global need for rebuilding marine life, the implementation of spawner sanctuaries using the criteria set forth herein may be a promising approach for restoring hard clam and other bivalve populations in estuaries elsewhere.

The long and narrow path for novel cell‐based seafood to reduce fishing pressure for marine ecosystem recovery - Benjamin S. Halpern; Jason Maier; Heather J. Lahr; Gordon Blasco; Christopher Costello; Richard S. Cottrell; Olivier Deschenes; Danielle M. Ferraro; Halley E. Froehlich; Gavin G. McDonald; Katherine D. Millage; Michael J. Weir (Fish and Fisheries, 2021)
Cell‐based seafood is an emerging novel food, with many start‐up companies aspiring for ocean conservation benefits through expanded market share that displaces wild‐caught seafood. However, the ability for cell‐based seafood to achieve this conservation outcome is often oversimplified and will rely on an extensive, and we find somewhat tenuous, chain of events. Here, we outline the technological, behavioural, market and ecological changes that must occur along this pathway, and conclude that fisheries recoveries and collateral ocean benefits are unlikely to result from cell‐based seafood technology. In particular, we detail nine necessary steps and argue that failure at any one step could hinder or even eliminate cell‐based seafood's conservation effects. We additionally draw comparisons to aquaculture and share broader lessons for other demand‐driven product interventions.

Integrating Place Attachment into Management Frameworks: Exploring Place Attachment Across the Recreation Opportunity Spectrum - Christopher J. Wynveen; Ingrid E. Schneider; Arne Arnberger; Stuart Cottrell; Eick von Ruschkowski (Environmental Management, 2020)
The importance of place in landscape management and outdoor recreation has been prominent in the literature since the 1970s. As such, calls to incorporate place into the management of parks, forests, and other protected areas exist. However, little work explores how place attachment may complement existing management frameworks. Hence, the purpose of this investigation was to explore levels of visitors’ place attachment intensity across the six classes of the Recreation Opportunity Spectrum (ROS). Survey data collected in North America and Europe indicated there was more similarity in place attachment intensities among areas classified toward the less developed end of the ROS, while greater variation existed among the more developed sites. Observing place attachment across all six ROS classes allowed for a deeper understanding of the correlation between place and the management framework.

Adaptive capacity in social–ecological systems: a framework for addressing bark beetle disturbances in natural resource management - Stuart Cottrell; Katherine M. Mattor; Jesse L. Morris; Christopher J. Fettig; Pavlina McGrady; Dorothy Maguire; Patrick M. A. James; Jennifer Clear; Zach Wurtzebach; Yu Wei; Andrea Brunelle; Jessica Western; et al. (Sustainability Science, 2020)

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Effect of feeding slowly fermentable grains on productive variables and amelioration of heat stress in lactating dairy cows in a sub-tropical summer - Paula A. Gonzalez-Rivas; Megan Sullivan; Jeremy J. Cottrell; Brian J. Leury; John B. Gaughan; Frank R. Dunshea (Tropical Animal Health and Production, 2018)

QTL analysis and genomic selection using RADseq derived markers in Sitka spruce: the potential utility of within family data - P. Fuentes-Utrilla; C. Goswami; J. E. Cottrell; R. Pong-Wong; A. Law; S. W. A’Hara; S. J. Lee; J. A. Woolliams (Tree Genetics & Genomes, 2017)

Phylogenetic and structural response of heterotrophic bacteria to dissolved organic matter of different chemical composition in a continuous culture study - M. Landa; M. T. Cottrell; D. L. Kirchman; K. Kaiser; P. M. Medeiros; L. Tremblay; N. Batailler; J. Caparros; P. Catala; K. Escoubeyrou; L. Oriol; S. Blain; et al. (Environmental Microbiology, 2014)
Summary Dissolved organic matter ( DOM ) and heterotrophic bacteria are highly diverse components of the ocean system, and their interactions are key in regulating the biogeochemical cycles of major elements. How chemical and phylogenetic diversity are linked remains largely unexplored to date. To investigate interactions between bacterial diversity and DOM , we followed the response of natural bacterial communities to two sources of phytoplankton‐derived DOM over six bacterial generation times in continuous cultures. Analyses of total hydrolysable neutral sugars and amino acids, and ultrahigh resolution mass spectrometry revealed large differences in the chemical composition of the two DOM sources. According to 454 pyrosequences of 16S ribosomal ribonucleic acid genes, diatom‐derived DOM sustained higher levels of bacterial richness, evenness and phylogenetic diversity than cyanobacteria‐derived DOM . These distinct community structures were, however, not associated with specific taxa. Grazing pressure affected bacterial community composition without changing the overall pattern of bacterial diversity levels set by DOM . Our results demonstrate that resource composition can shape several facets of bacterial diversity without influencing the phylogenetic composition of bacterial communities, suggesting functional redundancy at different taxonomic levels for the degradation of phytoplankton‐derived DOM .

Metagenomic analysis of organic matter degradation in methane‐rich Arctic Ocean sediments - David L. Kirchman; Thomas E. Hanson; Matthew T. Cottrell; Leila J. Hamdan (Limnology and Oceanography, 2014)
Organic material is degraded anaerobically by a complex community of microbes making up the anaerobic food chain. This community was examined in methane‐rich sediments of the Beaufort Sea, Alaska, using metagenomic sequencing, along with tag pyrosequencing and quantitative polymerase chain reaction analyses of 16S ribosomal ribonucleic acid genes. The goal of the study was to examine the relative abundance and taxonomic composition of organisms making up different parts of the anaerobic food chain. The metagenomic data suggested that genes for producing acetate via fermentation (“acetate fermentation”) were more common than genes producing other fermentation by‐products, but acetate fermentation genes made up only 32% of all genes for fermentation pathways while genes for fermentation to ethanol accounted for 27%. The genes for the production of other compounds, including propionate (15%), butyrate (11%), lactate (4%), and hydrogen gas (11%), were also often abundant. Similar results were observed when the same approach was used to analyze metagenomic data previously collected from two low‐latitude systems with methane‐rich sediments. In all of these sediments, genes for pathways producing organic acids, ethanol, and hydrogen gas were about 30‐fold more abundant than the genes for sulfate reduction and methanogenesis, processes which consume those compounds. Our results suggest that the type and abundance of fermentative microbes potentially affect the taxonomic composition of sulfate‐reducing bacteria and methanogenic archaea and rates of organic carbon mineralization by the anaerobic food chain.

Predicting Stakeholder Support for Fishery Policies - Arren Mendezona Allegretti; Jerry J. Vaske; Stuart Cottrell (Coastal Management, 2012)

Bronfenbrenner’s bioecological theory for modelling community resilience to natural disasters - Helen J. Boon; Alison Cottrell; David King; Robert B. Stevenson; Joanne Millar (Natural Hazards, 2012)

Local magnetism in palladium bionanomaterials probed by muon spectroscopy - Neil J. Creamer; Iryna P. Mikheenko; Clive Johnson; Stephen P. Cottrell; Lynne E. Macaskie (Biotechnology Letters, 2011)

Erratum to: Tree Height Influences Flight of Lesser Peachtree Borer and Peachtree Borer (Lepidoptera: Sesiidae) Males - Ted E. Cottrell; D. L. Horton; J. Fuest (Journal of Insect Behavior, 2010)

Tree Height Influences Flight of Lesser Peachtree Borer and Peachtree Borer (Lepidoptera: Sesiidae) Males - Ted E. Cottrell; D. L. Horton; J. Fuest (Journal of Insect Behavior, 2010)

Molecular biodiversity and population structure in common ash (Fraxinus excelsior L.) in Britain: implications for conservation - B. G. SUTHERLAND; A. BELAJ; S. NIER; J. E. COTTRELL; S. P VAUGHAN; J. HUBERT; K. RUSSELL (Molecular Ecology, 2010)

Light‐dependent growth and proteorhodopsin expression by Flavobacteria and SAR11 in experiments with Delaware coastal waters - Raphaël Lami; Matthew T. Cottrell; Barbara J. Campbell; David L. Kirchman (Environmental Microbiology, 2009)
Summary Proteorhodopsin (PR)‐containing bacteria are hypothesized to use both light and organic compounds as energy sources. Recent studies have found that PR is common in marine microorganisms, but the impact of light on the growth of PR‐containing organisms and PR transcription in the environment remains unclear. We examined the diversity of PR genes and transcripts by PCR amplification and sequencing in Delaware coastal waters. Clone libraries of PR DNA and cDNA (from mRNA) revealed large differences between bacterial groups in expression of PR genes. We then evaluated by quantitative PCR the impact of light on growth and PR expression in PR‐containing SAR11 bacteria (SAR11‐PR) and a population of Flavobacteria ( Flavobacteria ‐PR). This experiment was conducted in 30 l microcosms exposed to continuous light, continuous dark, and 12 h−12 h dark–light cycles for 5 days. We found a strong upregulation of PR expression by light in Flavobacteria ‐PR and SAR11‐PR. The abundance of PR transcripts per PR cell was enhanced up to 120‐fold under continuous light and up to 20‐fold under dark–light cycles while continuous darkness led to very low levels of PR mRNA. This upregulation of PR expression was correlated with the abundance of PR genes, indicating net growth of SAR11‐PR cells and Flavobacteria ‐PR under dark–light cycles. SAR11‐PR and Flavobacteria ‐PR abundance decreased under continuous light despite upregulation of PR expression, and continuous darkness led to low abundances of both populations. Collectively, these data suggest that light affects growth of PR‐containing bacteria and regulation of PR mRNA synthesis in natural communities.

Abundant proteorhodopsin genes in the North Atlantic Ocean - Barbara J. Campbell; Lisa A. Waidner; Matthew T. Cottrell; David L. Kirchman (Environmental Microbiology, 2008)
Summary Proteorhodopsin (PR) is a light‐driven proton pump that has been found in a variety of marine bacteria, including Pelagibacter ubique , a member of the ubiquitous SAR11 clade. The goals of this study were to explore the diversity of PR genes and to estimate their abundance in the North Atlantic Ocean using quantitative polymerase chain reaction (QPCR). We found that PR genes in the western portion of the Sargasso Sea could be grouped into 27 clusters, but five clades had the most sequences. Sets of specific QPCR primers were designed to examine the abundance of PR genes in the following four of the five clades: SAR11 ( P. ubique and other SAR11 Alphaproteobacteria ), BACRED17H8 ( Alphaproteobacteria ), HOT2C01 ( Alphaproteobacteria ) and an uncultured subgroup of the Flavobacteria . Two groups (SAR11 and HOT2C01) dominated PR gene abundance in oligotrophic waters, but were significantly less abundant in nutrient‐ and chlorophyll‐rich waters. The other two groups (BACRED17H8 and Flavobacteria subgroup NASB) were less abundant in all waters. Together, these four PR gene types were found in 50% of all bacteria in the Sargasso Sea. We found a significant negative correlation between total PR gene abundance and nutrients and chlorophyll but no significant correlation with light intensity for three of the four PR types in the depth profiles north of the Sargasso Sea. Our data suggest that PR is common in the North Atlantic Ocean, especially in SAR11 bacteria and another marine alphaproteobacterial group (HOT2C01), and that these PR‐bearing bacteria are most abundant in oligotrophic waters.

Ex-situ conservation of Black poplar in Europe: genetic diversity in nine gene bank collections and their value for nature development - V. Storme; A. Vanden Broeck; B. Ivens; D. Halfmaerten; J. Van Slycken; S. Castiglione; F. Grassi; T. Fossati; J. E. Cottrell; H. E. Tabbener; F. Lefèvre; C. Saintagne; et al. (Theoretical and Applied Genetics, 2004)

Petrologic and experimental evidence for the movement and heating of the pre-eruptive Minoan rhyodacite (Santorini, Greece) - Elizabeth Cottrell; James E. Gardner; Malcolm J. Rutherford (Contributions to Mineralogy and Petrology, 1999)

A stochastic model of retinotopy: A self organizing process - M. Cottrell; J. C. Fort (Biological Cybernetics, 1986)